Ligation-assisted endoscopic mucosal resection for esophageal granular cell tumors is safe and effective. Issue 8 (25th May 2020) - Kumar, Shria; Chandrasekhara, Vinay; Kochman, Michael L; Ahmad, Nuzhat; Attalla, Sara; Ho, Immanuel K; Jaffe, David L; Lee, Peter J; Panganamamula, Kashyap V; Saumoy, Monica; Fortuna, Danielle; Ginsberg, Gregory G
SUMMARY: Given their malignant potential, resection of esophageal granular cell tumors (GCTs) is often undertaken, yet the optimal technique is unknown. We present a large series of dedicated endoscopic resection using band ligation (EMR-B) of esophageal GCTs. Patients diagnosed with esophageal GCTs between 2002 and 2019 were identified using a prospectively collected pathology database. Endoscopic reports were reviewed, and patients who underwent dedicated EMR-B of esophageal GCTs were included. Medical records were queried for demographics, findings, adverse events, and follow-up. We identified 21 patients who underwent dedicated EMR-B for previously identified esophageal GCT. Median age was 39 years; 16 (76%) were female. Eight (38%) had preceding signs or symptoms, potentially attributable to the GCT. Upon endoscopic evaluation, 12 (57%) were found in the distal esophagus. Endoscopic ultrasound was used in 15 cases (71%). Median lesion size was 7 mm, interquartile range 4 mm—8 mm. The largest lesion was 12 mm. A total of 20 (95%) had en bloc resection confirmed with pathologic examination. The only patient with tumor extending to the resection margin underwent surveillance endoscopy that showed no residual tumor. No patients experienced bleeding, perforation, or stricturing in our series. No patients have had known recurrence of their esophageal GCT. EMR-B of esophageal GCT achieves complete histopathologic resection with minimal adverse events. EMR-B is safe and effective and seems prudent compared with observation for what could be an aggressive and malignant tumor. EMR-B should be considered first-line therapy when resecting esophageal GCT up to 12 mm in diameter.